Modified ethylene propylene diene monomer, preparation method and application
By introducing α-olefins to modify the EPDM rubber, a three-dimensional network structure is formed, which solves the problem of insufficient tolerance of EPDM in extreme environments, and realizes an EPDM rubber that is suitable for extreme environments in a wider range.
Patent Information
- Application Number
- CN202411914921.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
The existing EPDM rubber (EPDM) cannot be used in extreme environments, and its reliability in extreme environments is low, making it impossible to break the service limit of existing EPDM base rubber strips.
By introducing α-olefins to modify EPDM rubber, the α-olefins are cross-linked with EPDM rubber to form a three-dimensional network structure, which improves the resistance of EPDM rubber to extreme environments.
It realizes the tolerance of EPDM rubber in extreme environments (from low temperature -48.1℃ to high temperature 158.3℃), widens its scope of application and extends its service life.
Smart Images

Figure CN119735747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a modified ethylene propylene diene monomer rubber, a preparation method and application thereof, and also relates to a material. Background Art
[0002] Ethylene propylene diene monomer (EPDM) is a terpolymer formed by copolymerization of ethylene, propylene and a small amount of a third monomer, wherein the mass fraction of ethylene is usually 45-75% and that of propylene is 25-55%. The unsaturation of commonly used EPDM is only 1-2% (molar fraction), which is equivalent to an unsaturated side group for every 200 carbon atoms on the main chain. Therefore, EPDM belongs to a carbon chain saturated non-polar rubber. Because its main molecular chain is saturated, EPDM has excellent resistance to ozone and thermal oxidation aging, as well as outstanding corrosion resistance, resistance to superheated water, electrical insulation and water resistance. It is widely used in the preparation of sealing strips, waterproof membranes, air conditioning hoses and wires and cables. However, the low temperature resistance of EPDM needs to be further improved in order to expand its application in extreme environments.
[0003] With the continuous development of science and technology, in the implementation of major projects such as aerospace, energy and resource development, extreme environments such as ultra-high temperature, ultra-low temperature, high / low temperature alternation are inevitable service environments for materials, which brings severe challenges to the high reliability and long service life of related devices. In this application context, it is urgent to develop a new generation of high-reliability EPDM-based rubber strips that are resistant to extreme environments, break through the service limits of existing EPDM-based rubber strips, and meet the major needs of future strategic projects.
[0004] In view of this, this patent application is filed. Summary of the invention
[0005] The purpose of this patent application is to solve the technical problems that the existing EPDM cannot be applied to extreme environments, has low reliability in extreme environment resistance, and cannot break through the service limit of the existing EPDM-based rubber strips.
[0006] The present invention is achieved through the following technical solutions:
[0007] The first object of the present invention is to provide a modified EPDM rubber, which is prepared from the following raw materials in parts by weight: 100 parts of EPDM rubber, 1 to 5 parts of plasticizer, 1 to 5 parts of vulcanizer, 1 to 5 parts of antioxidant, 0.1 to 1 part of accelerator, 1 to 10 parts of cross-linking agent, 10 to 100 parts of reinforcing agent, and 1 to 30 parts of α-olefin.
[0008] In the present invention, α-olefin is used to modify EPDM rubber. The α-olefin and EPDM rubber are cross-linked to form a three-dimensional network structure, which improves the tolerance of EPDM rubber to extreme environments (from low temperature of -48.1°C to high temperature of 158.3°C), thereby achieving the purpose of expanding the application range of EPDM rubber in extreme environments and extending its service life.
[0009] In the present invention, the main function of the plasticizer is to weaken the intermolecular forces of the polymer, reduce the melting temperature and viscosity of the polymer, thereby improving the compatibility and processing performance of the EPDM rubber. In addition, the plasticizer can also reduce the hardness of the rubber, giving it higher elasticity and cold resistance, thereby improving the physical and mechanical properties of the final product.
[0010] Vulcanizing agent: It can make rubber molecules form a three-dimensional network structure, enhancing its mechanical strength and durability.
[0011] Antioxidants: They can absorb harmful free radicals produced during the vulcanization process, reduce scorching, and extend the service life of rubber. Antioxidants can also significantly affect the cross-linking density of vulcanized rubber, thereby adjusting the aging resistance of rubber.
[0012] Accelerator: can accelerate the vulcanization reaction, increase the vulcanization rate, and improve the performance of the vulcanized rubber.
[0013] Cross-linking agent: helps to form a more stable cross-linking network structure, thereby improving the heat resistance and mechanical strength of the rubber.
[0014] Reinforcement agent: can significantly improve the mechanical properties of EPDM rubber.
[0015] α-Olefin: It is used in the present invention to regulate the glass transition temperature of EPDM rubber. The introduction of flexible α-olefin chains can significantly change the glass transition temperature of EPDM rubber, mainly by increasing the flexibility of the molecular chain, and this increase in flexibility makes the molecular chain easier to rotate and vibrate at low temperatures, thereby reducing Tg. This is because the presence of flexible segments reduces the constraints between molecular segments, making it easier for the segments to thaw and start moving. Therefore, the introduction of flexible segments in the present invention reduces the regularity and crystallization ability of the entire molecular chain, reduces the interaction force between molecules, and allows the material to achieve free movement of segments at lower temperatures.
[0016] In the present invention, the weight fractions of each component are reasonably designed to ensure that the final rubber material has good mechanical properties and temperature resistance. The synergistic effect of each component enables the final rubber to have excellent temperature resistance.
[0017] Furthermore, the reinforcing agent consists of zinc oxide and silicon dioxide, and the weight ratio of zinc oxide to silicon dioxide is 1:1-5.
[0018] The main function of adding zinc oxide (ZnO) to EPDM is to act as an activator and vulcanizing agent to promote the vulcanization process of the rubber. Zinc oxide can increase the crosslinking degree of the rubber, reduce the number of sulfur atoms in the crosslinking bonds, and thus improve the crosslinking density. This helps to improve the aging resistance and mechanical strength of the vulcanized rubber. Silicon dioxide is used as a reinforcing agent for EPDM. Its reinforcing mechanism is mainly achieved by forming a three-dimensional physical crosslinking network, which connects clusters to EPDM molecular segments by van der Waals adsorption, thereby improving the mechanical properties of the material.
[0019] Furthermore, the α-olefin is selected from hexene, octene, dodecene, tetradecene, hexadecene or octadecene.
[0020] As for high temperature resistance, EPDM itself has good high temperature resistance, which is closely related to its molecular structure. First of all, EPDM is a terpolymer composed of ethylene, propylene and non-conjugated dienes. Its main molecular chain is a fully saturated straight chain structure without double bonds, which enables it to maintain stable chemical properties at high temperatures.
[0021] For low temperature resistance, as mentioned above, the key to enable the final rubber material to break through the performance limit of traditional EPDM under extreme environment (under low temperature environment) lies in the introduction of flexible alpha-olefins. In EPDM, by introducing flexible alpha-olefin chains by irradiation, the flexibility of the molecular chain can be increased, thereby reducing the intermolecular interaction force, reducing the constraint between the molecular segments, making the segments easier to thaw and start to move. In addition, the composition of the copolymer can also be controlled by regulating the type and ratio of alpha-olefins, and then regulating its Tg. In the present invention, by selecting suitable alpha-olefin monomer types (hexene, octene, dodecene, tetradecene, hexadecene or octadecene) and ratio, the Tg of EPDM can be accurately regulated so that it is more prominent in low temperature resistance.
[0022] Furthermore, the plasticizer is stearic acid; and / or the auxiliary cross-linking agent is triallyl isocyanurate;
[0023] and / or the vulcanizing agent is a peroxide vulcanizing agent;
[0024] and / or the antioxidant is antioxidant RD;
[0025] And / or the accelerator is accelerator M or accelerator DM.
[0026] Furthermore, the peroxide vulcanizing agent is DCP or BIBP.
[0027] When preparing ethylene propylene diene monomer rubber (EPDM), selecting vulcanizing agent DCP, antioxidant RD, accelerator DM and plasticizer stearic acid has certain advantages.
[0028] Vulcanizing agent DCP has high cross-linking efficiency and low cost. It can significantly improve the physical properties of rubber, such as strength and durability.
[0029] Antioxidant RD can effectively improve the heat-oxidative aging resistance of rubber. Under high temperature conditions, the selection of antioxidant is particularly important, and RD can provide good anti-aging effects.
[0030] Accelerator DM can accelerate the vulcanization speed and improve the physical properties of vulcanized rubber. Studies have shown that appropriate DM dosage can increase the tensile strength of EPDM.
[0031] Plasticizer Stearic acid is not only used as a plasticizer, but also has multiple functions such as lubrication, stability and anti-oxidation. It can improve the processing performance and physical properties of products, while improving weather resistance and corrosion resistance. In EPDM formulas, stearic acid helps to improve the softness and ductility of the material.
[0032] The inventors found in their research that different vulcanization systems and antioxidants have a significant impact on the performance of EPDM. For example, the use of a non-peroxide vulcanization system may result in a decrease in heat resistance and aging resistance. In addition, some antioxidants may not provide sufficient antioxidant protection, resulting in rapid aging of the product under high temperature or harsh conditions. At the same time, some alternative materials may not be compatible with the chemical structure of EPDM, resulting in unstable material properties or frosting. For example, the solubility of sulfur in EPDM is extremely low, which easily leads to frosting problems. Therefore, the selection of these specific chemical substances in the present invention is to optimize the comprehensive performance of EPDM, including improving its physical properties, vulcanization speed, aging resistance, and low temperature resistance.
[0033] In summary, the selection of the specific formula in the present invention, such as the vulcanizing agent, antioxidant and accelerator, can ensure that the EPDM rubber products have excellent physical and mechanical properties, heat resistance and aging resistance, while avoiding the problems of increased costs and process complexity.
[0034] A second object of the present invention is to provide a method for preparing a modified EPDM rubber, comprising the following steps:
[0035] (1) mixing EPDM rubber, plasticizer, vulcanizer, antioxidant, accelerator, co-crosslinking agent and reinforcing agent and kneading;
[0036] (2) refining the rubber compound after internal mixing;
[0037] (3) hot pressing and cold pressing the rubber material after kneading in sequence;
[0038] (4) The molded rubber is mixed with α-olefin and irradiated with γ-rays to obtain α-olefin modified EPDM rubber.
[0039] In the present invention, α-olefin is used as a modifier, mixed with EPDM, and then irradiated with gamma rays. This method utilizes the chemical properties of α-olefin, and initiates a chemical reaction between α-olefin and EPDM through gamma ray irradiation, thereby achieving modification. This is different from the traditional radiation cross-linking method, which usually does not involve a specific modifier, but directly initiates a cross-linking reaction between polymer molecules through radiation.
[0040] Furthermore, the banburying temperature in step (1) is 100-120° C., the banburying time is 10-30 min, and the banburying speed is 10-50 rpm;
[0041] And / or during the banburying in step (1), the EPDM rubber is first heated to the banburying temperature, and then a plasticizer, a vulcanizing agent, an antioxidant, an accelerator, a co-crosslinking agent and a reinforcing agent are added and mixed;
[0042] And / or place at 20-35℃ for 24-48h after internal mixing.
[0043] The conventional rubber refining temperature is usually above 120°C, even up to 160-180°C, and the refining time is short (no more than 2 minutes). However, in this patent, the refining temperature is 100-120°C. This lower temperature helps to reduce the oxidative cracking of rubber molecules, thereby maintaining good physical and mechanical properties. In addition, the selection of a refining time of 10-30 minutes helps to better disperse and mix various compounding agents, improve the uniformity and quality of the final product, and make the final product have better physical and mechanical properties.
[0044] Furthermore, in step (2), the rotation speed ratio of the front and rear rollers during the training is 1 to 2:1;
[0045] And / or in step (2), the temperature of the opening refining is 90-100°C;
[0046] And / or in step (2), the mill is thinned at least 5 times during the refining.
[0047] In the present invention, the stability and durability of the material under extreme temperature conditions can be further improved by finely controlling the conditions for opening and refining. For example, a lower opening and refining temperature helps prevent degradation caused by high temperature, while an appropriate number of thin passes helps improve the uniformity of the material, thereby enhancing its mechanical properties and durability under different temperatures.
[0048] Furthermore, in step (3), the temperature of the hot pressing molding is 100 to 120° C., the time of the hot pressing molding is 1 to 5 min, and the pressure of the hot pressing molding is 10 to 50 MPa;
[0049] And / or in step (3), the temperature of the cold press molding is 20-30° C., the time of the cold press molding is 1-5 min, and the pressure of the cold press molding is 10-50 MPa.
[0050] The temperature range of the hot pressing molding in the present invention is 100-120°C, the time is 1-5 minutes, and the pressure is 10-50MPa. High temperature and high pressure help to improve the density and strength of the material, and also can better control the microstructure of the material, thereby improving its high and low temperature resistance.
[0051] The temperature range of cold pressing is 20-30℃, the time is 1-5 minutes, and the pressure is 10-50MPa. Low temperature and high pressure help to maintain the original structure of the material, reduce thermal stress, and thus improve the low temperature resistance of the material.
[0052] Furthermore, in step (4), before irradiation with gamma rays, the formed rubber material is mixed with the α-olefin and allowed to stand for 48 to 72 hours;
[0053] And / or in step (4), the irradiation dose of gamma rays is 10 to 300 kGy;
[0054] and / or in step (4), the gamma ray has an activity of 2.59×10 15 Bq 60 Co γ-rays;
[0055] And / or in step (4), the irradiation dose rate of gamma rays is 100 Gy / min.
[0056] In the present invention, the irradiation of a higher dose of gamma rays can significantly change the molecular structure and microscopic morphology of the material, thereby improving the high and low temperature resistance of the material. 60Co gamma rays with an activity of 2.59×10^15Bq are used. 60Co gamma rays have the characteristics of strong penetration and high energy, and are suitable for processing materials of large size and complex structure. This type of gamma ray can penetrate deep into the material and uniformly change the microstructure of the material, thereby improving its high and low temperature resistance.
[0057] The third object of the present invention is to provide an application of the modified EPDM rubber described in any one of the above items for preparing low-temperature and / or high-temperature resistant materials, wherein the low temperature is -48.1°C to -40°C and the high temperature is 89°C to 158°C.
[0058] The fourth object of the present invention is to provide a material, the raw material of which includes any one of the modified EPDM rubbers described above.
[0059] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0060] The present invention utilizes α-olefin to modify EPDM rubber. The α-olefin and EPDM rubber are cross-linked to form a three-dimensional network structure, thereby improving the tolerance of EPDM rubber to extreme environments (from low temperature -48.1°C to high temperature 158.3°C), thereby achieving the purpose of expanding the application range of EPDM rubber in extreme environments and extending its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0062] Figure 1 The present invention is a flow chart for preparing α-olefin-EPDM rubber (EORX-Y).
[0063] Figure 2 Infrared spectra of α-olefins and EOR7001-Y containing different α-olefin structural units: A is hexene; B is octene; C is dodecene; D is tetradecene; E is hexadecene; and F is octadecene.
[0064] Figure 3 The infrared spectra of EOR7001-18 prepared under different radiation doses.
[0065] Figure 4 The temperature spectrum of dynamic mechanical properties of EOR7001-Y containing different types of α-olefin structural units. Among them, storage modulus refers to storage modulus, and loss modulus refers to loss modulus.
[0066] Figure 5 The mechanical loss-temperature curve of EOR7001-Y containing different types of α-olefin structural units and a schematic diagram of the glass transition temperature of EOR7001-Y changing with the number of α-olefin carbon atoms: A is the mechanical loss-temperature curve; B is a schematic diagram of the glass transition temperature changing with the number of α-olefin carbon atoms.
[0067] Figure 6 The thermal gravimetric analysis results of EOR7001-Y with different α-olefin carbon chain lengths: A is the thermal gravimetric curve (TGA); B is the differential thermal gravimetric curve (DTG).
[0068] Figure 7 Mechanical properties of EOR7001-Y prepared from different α-olefins: A is tensile strength; B is elongation at break. DETAILED DESCRIPTION
[0069] The following embodiments further describe the implementation of the present application in detail. The detailed description of the following embodiments is used to illustrate the principle of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.
[0070] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.
[0071] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0072] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0073] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0074] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0075] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0076] The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.
[0077] The ethylene propylene diene monomer rubber used in the present invention is EPDM7001, wherein the content of ethylene structural units is 73w%, and the content of the third monomer ethylidene norbornene is 5w%.
[0078] Example 1: Preparation of α-olefin-EPDM rubber (EORX-Y)
[0079] The process of preparing α-olefin-EPDM rubber (irradiated α-Olefin-EPDM, referred to as EORX-Y, where X represents the EPDM grade and Y represents the carbon chain length of the α-olefin, such as EOR7001-6, which means that the EPDM used is EPDM7001 and the α-olefin is hexene) by irradiation crosslinking is as follows: Figure 1 shown.
[0080] First, the EPDM raw rubber was mixed on a Haake mixer, the mixing temperature was controlled at 100°C, and the speed was 30rpm. After the material (EPDM) temperature rose to 100°C, stearic acid (SA), zinc oxide (ZnO), antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer), accelerator DM (dibenzothiazole disulfide), co-crosslinking agent TAIC (triallyl isocyanurate), vulcanizing agent BIBP and silicon dioxide (basic experimental formula is shown in Table 1), mixed for 10 minutes, unloaded, and placed at room temperature (20-35°C) for 24 hours.
[0081] Afterwards, the rubber material was mixed using a double-roll open mill with a front and rear roll speed ratio of 1.2:1 and a mixing temperature of 90°C. It was thinned ten times and sheeted. It was then processed and formed using a hot press with a molding temperature of 120°C, a molding time of 3 minutes and a molding pressure of 20 MPa.
[0082] After the hot pressing is completed, a cold press is used to quickly cool down the temperature. The cold pressing temperature is 25°C, the cold pressing time is 3 minutes, and the molding pressure is 10MPa. After the sample is placed at room temperature for 24 hours, it is cut into dumbbell-shaped or rectangular splines by a punching machine, which is the EPDM spline.
[0083] Table 1. Basic formula of the experiment of the present invention (based on EPDM, EPDM is 100phr)
[0084]
[0085] Secondly, a certain amount of α-olefin (hexene, octene, dodecene, tetradecene, hexadecene or octadecene) was weighed and fully contacted with the above EPDM strips in a closed container (the amount of α-olefin was 5phr, 10phr, 15phr, 20phr or 25phr, and the amount of EPDM was 100phr), and placed at room temperature for 48h; finally, the above strips were placed in a closed container and a 2.59×10 15Bq 60 The sample prepared by irradiating in a Coγ irradiation field at a set dose (10 kGy, 50 kGy, 100 kGy, 150 kGy, 200 kGy or 250 kGy) and a dose rate of 100 Gy / min is irradiated as irradiation cross-linked α-olefin-EPDM rubber (EORX-Y).
[0086] Test Example 1: Attenuated Total Reflection Infrared Spectroscopy (ATR) Test of EORX-Y of the Present Invention
[0087] 1. Experimental methods
[0088] Infrared spectroscopy (FT-IR) is an effective method for characterizing the structure of a substance. In this experiment, a Thermo Nicolet 670 Fourier transform infrared spectrometer was used to characterize the structure of the sample prepared according to the method described in Example 1. The sample was tested using the ATR attenuated total reflection method, and the wave number measurement range was 600 to 4000 cm -1 .
[0089] 2. Experimental results
[0090] 2.1 Infrared spectroscopy characterization of EORX-Y prepared from different α-olefin structural units
[0091] Figure 2 It is the infrared spectra of α-olefin and EORX-Y containing different α-olefin structural units (EPDM7001 is used as the research matrix). When the α-olefin (hexene, octene, dodecene, tetradecene, hexadecene or octadecene) is changed, the α-olefin content is fixed at 10phr and the radiation dose is 100kGy.
[0092] Figure 2 A, B, C, D, E, and F are the products obtained by radiation cross-linking hexene, octene, dodecene, tetradecene, hexadecene, and octadecene based on EPDM7001, respectively. The cross-linked products have very similar infrared spectra characteristics.
[0093] like Figure 2 As shown in the figure, all α-olefins have stretching vibrations of carbon-carbon double bonds (C=C) and unsaturated carbon-hydrogen bonds (=CH). The former is at 1640-1670 cm -1 Characteristic absorption peaks appear in the range of 3010~3100cm -1The characteristic absorption peak appears in the range of 100%; similarly, the double bond of the side chain of uncrosslinked EPDM7001 also has a similar infrared spectrum characteristic absorption peak. By comparison, it is found that there is no similar double bond characteristic absorption peak in the infrared spectra of all EORX-Y, which proves that the double bonds in α-olefins and EPDM are opened under the action of radiation and participate in the formation of new chemical bonds, which means the formation of a three-dimensional network structure in EORX-Y. The three-dimensional network structure forms a more solid and stable molecular chain through cross-linking reaction, which enables the material to better disperse stress when subjected to external force, thereby improving its mechanical strength and durability. Secondly, this structure can effectively limit the movement of molecular chains and reduce the relative slip between molecules, thereby improving the thermal stability and creep resistance of the material. Under high temperature conditions, the three-dimensional network structure can effectively inhibit the thermal movement of molecular chains and prevent the molecular chains from breaking or reorganizing due to the increase in temperature, thereby maintaining the shape and performance of the material. In low temperature environments, this structure can provide additional rigid support to prevent the material from becoming too brittle due to low temperature, resulting in breakage or cracking. In addition, the three-dimensional network structure can also enhance the chemical stability of the material and reduce the chemical degradation that may occur under extreme temperature conditions.
[0094] by Figure 2 For example, the stretching vibration characteristic absorption peak of the carbon-carbon double bond (C=C) of octadecene is 1641 cm -1 The characteristic absorption peak of the stretching vibration of unsaturated carbon-hydrogen bond (=CH) is 3076cm -1 ; 722cm -1 -(CH2) n -(n>4) CH rocking vibration absorption peak; 908cm -1 and 992cm -1 It is the bending vibration absorption peak of vinyl unsaturated carbon-hydrogen bond (=CH); 1370cm -1 It is the symmetrical bending vibration absorption peak of C-CH3-; 1459cm -1 It is the shear vibration absorption peak of CH in methylene; 2856cm -1 and 2924cm -1 The characteristic absorption peak of the stretching vibration of the carbon-carbon double bond (C=C) of uncrosslinked EPDM7001 is 1649 cm -1 The characteristic absorption peak of the stretching vibration of unsaturated carbon-hydrogen bond (=CH) is 3010cm -1 ; 723cm -1 -(CH2) n -(n>4) CH rocking vibration absorption peak; 1378cm -1 It is the symmetrical bending vibration absorption peak of C-CH3-; 1465cm -1It is the shear vibration absorption peak of CH in methylene; 2852cm -1 and 2921cm -1 It is the stretching vibration absorption peak of two CH in methylene. The infrared spectrum characteristic absorption peaks of radiation cross-linked product EOR7001-18 are assigned as follows: 722cm -1 -(CH2) n -(n>4) CH rocking vibration absorption peak; 1373cm -1 It is the symmetrical bending vibration absorption peak of C-CH3-; 1459cm -1 It is the shear vibration absorption peak of CH in methylene; 2852cm -1 and 2918cm -1 It is the stretching vibration absorption peak of two CH in methylene; 1096cm -1 and 807cm -1 It is the stretching vibration absorption peak of the auxiliary silica in EOR7001-18; in comparison, the stretching vibration characteristic absorption peak of the carbon-carbon double bond (C=C) and the stretching vibration characteristic absorption peak of the unsaturated carbon-hydrogen bond (=CH) disappeared in the radiation cross-linked product EOR7001-18, indicating that octadecene and EPDM7001 underwent a grafting polymerization reaction or octadecene formed a homopolymer.
[0095] In addition, after extraction, the homopolymer and small molecules formed by octadecene in EOR7001-18 have been removed, and the remaining part is pure EOR7001-18 gel, which proves that octadecene and EPDM7001 form a cross-linked network structure under the action of gamma rays.
[0096] The extraction experiment process mentioned above: Weigh a certain mass of dry EORX-Y rubber, wrap the sample with filter paper, and put it into the Soxhlet extractor. Use tetrahydrofuran to reflux at 66°C for 24 hours to extract the sample, then put it into a vacuum oven at 60°C to dry for 24 hours, and take it out for infrared spectrum detection according to the experimental method.
[0097] 2.2 Infrared spectroscopy characterization of EORX-Y prepared with different radiation doses
[0098] Taking octadecene as an example, Figure 3 The infrared spectra of EOR7001-18 (prepared by irradiation cross-linking EPDM7001 and octadecene, wherein the octadecene content is 20 phr) prepared under different radiation dose conditions (0 kGy, 50 kGy, 100 kGy, 150 kGy, 200 kGy, 250 kGy).
[0099] Figure 3It can be seen that with the increase of radiation dose, the position and intensity of the characteristic absorption peak of EOR7001-18 did not change significantly. Therefore, infrared spectroscopy can only qualitatively characterize EORX-Y, proving that EPDM and octadecene undergo a chemical cross-linking reaction, but cannot quantitatively characterize the effect of radiation dose on the structure of EORX-Y.
[0100] The infrared spectrum shows that α-olefin and EPDM can successfully undergo cross-linking reaction under the action of γ-rays, forming a cross-linked network structure inside the obtained EORX-Y.
[0101] Test Example 2: Determination of Dynamic Mechanical Properties (DMA) of EORX-Y of the Present Invention
[0102] 1. Experimental methods
[0103] Dynamic mechanical properties were tested using DMA Q800. The relationship between the modulus of EORX-Y (prepared according to the method described in Example 1) at a certain frequency and temperature was determined using a uniaxial tensile mode. The test sample size was 20 mm × 10 mm × 1 mm, the heating rate was controlled at 3 ° C / min, the scanning temperature range was set to -75 ~ 150 ° C, the loading frequency was 1 Hz, and the loading amplitude was 15 μm.
[0104] 2. Experimental results
[0105] 2.1 Effect of α-olefin carbon chain length on dynamic mechanical properties
[0106] Taking EPDM7001 as matrix and silica content of 20phr, the effect of carbon chain length of different types of α-olefins on the dynamic mechanical properties of EORX-Y was studied. Figure 4 It is the temperature spectrum of dynamic mechanical properties of EOR7001-Y containing different types of α-olefin structural units, among which EOR7001-6, EOR7001-8, EOR7001-12, EOR7001-14, EOR7001-16 and EOR7001-18 are the products of radiation cross-linking of EPDM7001 with hexene, octene, dodecene, tetradecene, hexadecene and octadecene respectively, the α-olefin content is 20phr and the radiation dose is 100kGy.
[0107] Uncrosslinked EPDM has three physical forms: glassy state, highly elastic state and viscous flow state. It is a typical amorphous polymer. Figure 4It can be seen that after EPDM7001 and different types of α-olefins undergo cross-linking reaction under 100kGy irradiation, the prepared EOR7001-Y still has two physical forms, glassy and elastic, but no longer has a viscous flow state. This is because EOR7001-Y has a cross-linked network structure inside, and the macromolecular chains cannot move freely, so EOR7001-Y cannot enter the viscous flow state. Around the glass transition temperature, EOR7001-Y enters the elastic state from the glassy state, the storage modulus changes by 4-6 orders of magnitude, and both tanδ and loss modulus reach maximum values, but the temperature corresponding to the tanδ peak (T g ) is greater than the temperature corresponding to the loss modulus peak.
[0108] In addition, from Figure 4 It can also be seen that when the carbon number of α-olefin is 6, 8, and 12, the mechanical loss peak of EOR7001-Y is relatively smooth, but the peak becomes wider as the carbon number increases; when the carbon number of α-olefin is 14, the mechanical loss peak of EOR7001-Y shows obvious tailing phenomenon, and the peak becomes wider; when the carbon number of α-olefin continues to increase to 16 and 18, the mechanical loss peak of EOR7001-Y shows a double peak phenomenon. The reasons for the above phenomenon are as follows: when the carbon number of α-olefin is small, the reactivity of the double bond is stronger, the degree of freedom during the polymerization reaction is higher, and the chain segment formed by radiation cross-linking is similar to the ethylene chain segment structure in EPDM. α-olefin can be well integrated into EPDM to form a homogeneous structure, showing a single peak curve in the DMA temperature spectrum. However, as the number of carbon atoms in α-olefins increases, the difference between the aggregated structure of α-olefins and the aggregated structure of ethylene segments and propylene segments in EPDM gradually becomes larger. The α-olefin segments can form their own aggregated structures independently. The formation of this aggregated state is manifested as the second mechanical loss peak in the DMA temperature spectrum, thus presenting a double-peak curve in the DMA temperature spectrum.
[0109] from Figure 5It can be seen from A that after adding α-olefin, the mechanical loss peak of EOR7001-Y decreases, and the corresponding glass transition temperature decreases. In general, chemical cross-linking bonds are formed between the molecular chains of the cross-linked product, the macromolecular chains cannot move freely, the rigidity increases, and the glass transition temperature increases. However, this experiment uses the radiation cross-linking method to prepare EPDM-based rubber. Under the action of radiation, the double bonds in EPDM are opened, and the more active α hydrogen in EPDM generates free radicals, causing EPDM to degrade and produce a "disentanglement" effect. After irradiation, the freedom of movement of the EPDM chain segment increases, and the glass transition temperature decreases; at the same time, the presence of α-olefin allows the degraded EPDM chain segment to react again. α-olefin plays a bridging role, increases the activity space of the chain segment, and also causes the glass transition temperature of EOR7001-Y to decrease.
[0110] from Figure 5 As can be seen from B, with the increase of the number of carbon atoms in α-olefins, the glass transition temperature of EOR7001-Y shows a trend of first decreasing and then increasing. When the number of carbon atoms in α-olefins is 12, the glass transition temperature of EOR7001-12 is the lowest, which is -48.1°C. The glass transition temperature of EOR7001 without α-olefins is -23.4°C. In comparison, the glass transition temperature of EOR7001-12 is reduced by 24.7°C. The low glass transition temperature of EOR7001-12 can ensure that it can still maintain good elasticity in extreme environments of about minus 40 degrees. Therefore, EOR7001-12 can be used as a special rubber for automobile tires, sealing materials, etc., and is expected to be used in industrial fields such as automobiles, aerospace, and shipbuilding. It can be seen that for EORX-Y products prepared by radiation cross-linking, not only can the low-temperature resistance of EPDM-based rubber be improved by the introduction of α-olefins, but also the low-temperature resistance can be regulated by changing the length of the α-olefin carbon chain to meet the use requirements under different conditions.
[0111] This test example shows that for EORX-Y products prepared by radiation cross-linking, the low-temperature resistance of EPDM-based rubber can be improved by introducing α-olefins. Among them, the low-temperature resistance of the EPDM-based rubber prepared by introducing 20phr dodecene at an irradiation dose of 100kGy is the best, which can ensure that it can still maintain good elasticity in an extreme environment of about minus 40℃ (as low as -48.1℃).
[0112] Test Example 3: Thermal stability test of EORX-Y of the present invention
[0113] 1. Experimental methods
[0114] The thermal stability of a series of EORX-Y rubbers (prepared according to the method described in Example 1) was tested and analyzed using an SDTQ600 thermal analyzer. The test conditions were as follows: sample mass was 2-3 mg, nitrogen atmosphere flow rate was 50 mL / min, test temperature was 25-600°C, and heating rate was 10°C / min.
[0115] 2. Experimental results
[0116] 2.1 Effect of α-olefin carbon chain length on TGA test results
[0117] Taking EPDM7001 as matrix and silica content of 20phr, the effect of α-olefin carbon chain length on the thermal weight loss properties of EORX-Y was studied (α-olefin content was fixed at 20phr and radiation dose was fixed at 100kGy). Figure 6 The TGA and DTG curves of EOR7001-Y with different α-olefin carbon chain lengths are shown in Figure 2. Figure 6 It can be seen that the three samples EOR7001-18, EOR7001-16, and EOR7001-14 all showed two thermal decomposition characteristic peaks, the first starting decomposition temperature was 158.3℃, 148.2℃, and 89.1℃, respectively, and the first maximum thermal decomposition temperature was 170.2℃, 160.6℃, and 129.5℃, respectively. However, EOR7001-12, EOR7001-10, and EOR7001-6 only showed one thermal decomposition characteristic peak, and the maximum decomposition temperatures were 473℃, 472℃, and 470℃, respectively. It can be seen that the addition of α-olefin has a certain effect on the thermal stability of EORX-Y. When the carbon chain length of α-olefin is ≤12, the steric hindrance of α-olefin itself is small, and it can evenly penetrate into the interior of the EPDM matrix, and it is not easy for it to self-polymerize to form an aggregated form. Therefore, EORX-Y has only one thermal decomposition characteristic peak, and EOR7001-12 has the largest peak. When the carbon chain length of α-olefin is ≥14, the steric hindrance of α-olefin itself is large, and the activity of the carbon chain is restricted. Therefore, α-olefin tends to self-polymerize to form a self-polymer aggregation form. The aggregate structure is significantly different from the structure of EPDM itself, so two thermal decomposition characteristic peaks are formed. The decomposition peak at low temperature affects the thermal stability of the product. Among them, EOR7001-12 has the best high temperature resistance.
[0118] It can be seen that the modified EPDM rubber of the present invention can withstand high temperatures (89.1-158.3° C.) in extreme environments, and is expected to meet the high temperature resistance requirements for applications in harsh environments.
[0119] Test Example 4: Mechanical Properties Test of EORX-Y of the Present Invention
[0120] 1. Experimental methods
[0121] The prepared EORX-Y rubber sample (prepared according to the method described in Example 1) was cut into a dumbbell shape and subjected to mechanical property testing using a CMT6104 microcomputer-controlled electronic universal testing machine. The tensile stress-strain performance test was conducted in accordance with the national standard GB / T 528-2009 "Test of tensile stress-strain performance of vulcanized rubber or thermoplastic rubber", the compressive stress-strain performance test was conducted in accordance with the national standard GB / T 7757-2009 "Test of compressive stress-strain performance of vulcanized rubber or thermoplastic rubber", the compression permanent deformation was measured in accordance with the national standard GB 7759-1996 "Compression permanent deformation of vulcanized rubber and thermoplastic rubber at room temperature, high temperature and low temperature", and the hardness was tested in accordance with the national standard GB / T 23651-2009 "Test of hardness of vulcanized rubber or thermoplastic rubber".
[0122] 2. Experimental results
[0123] 2.1 Effect of α-olefin carbon chain length on tensile strength and elongation at break
[0124] EOR7001-Y was prepared with EPDM7001 as the matrix and a silica content of 20 phr. The effect of α-olefin carbon chain length on the mechanical properties of EORX-Y was studied (α-olefin content was fixed at 20 phr and radiation dose was fixed at 100 kGy).
[0125] Figure 7 The tensile strength (A) and elongation at break (B) of EOR7001-Y prepared from different α-olefins (measured at a standard temperature of 23±2°C). As can be seen from the figure, with the increase in the number of carbon atoms in α-olefins, the tensile strength of EOR7001-Y first increases and then decreases, and the elongation at break gradually decreases. Compared with the control sample EOR7001 without the introduction of α-olefins, the tensile strength of EOR7001-Y has decreased to varying degrees, with a reduction percentage of 12 to 32%, but the elongation at break has been greatly improved, with an increase percentage of 88 to 188%. This shows that the introduction of α-olefins will reduce the tensile strength of the EPDM matrix to a certain extent, but will significantly increase its elongation at break. The type of α-olefin can be adjusted according to subsequent use requirements to ensure that while maintaining the tensile strength of the EOR7001-Y matrix, its elongation at break is improved.
[0126] The results of mechanical properties test show that after the introduction of α-olefin, although the tensile strength of EOR7001-based rubber is reduced to a certain extent (the reduction percentage is 12-32%), the elongation at break is greatly improved (the increase percentage is 88-188%), indicating that the deformation ability is greatly improved, making it more suitable for use as a substrate for deformation compensation devices.
[0127] In summary, the present invention successfully prepares α-olefin modified EPDM rubber by radiation crosslinking, and can regulate and optimize the low temperature resistance and high temperature resistance of EPDM rubber by controlling the type of α-olefin, wherein when the α-olefin is dodecene, the prepared EPDM rubber has the best low temperature resistance and high temperature resistance. The present invention improves the tolerance of EPDM rubber to extreme environments, thereby achieving the purpose of broadening the scope of application of EPDM rubber in extreme environments and extending its service life.
[0128] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A modified EPDM rubber, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of EPDM rubber, 1-5 parts of plasticizer, 1-5 parts of vulcanizer, 1-5 parts of antioxidant, 0.1-1 part of accelerator, 1-10 parts of cross-linking agent, 10-100 parts of reinforcing agent and 1-30 parts of alpha-olefin.
2. The modified EPDM rubber according to claim 1, characterized in that: The reinforcing agent consists of zinc oxide and silicon dioxide, and the weight ratio of zinc oxide to silicon dioxide is 1:1-5.
3. The modified EPDM rubber according to claim 1, characterized in that: The α-olefin is selected from hexene, octene, dodecene, tetradecene, hexadecene or octadecene.
4. The modified EPDM rubber according to claim 1, characterized in that: The plasticizer is stearic acid; and / or the auxiliary cross-linking agent is triallyl isocyanurate; and / or the vulcanizing agent is a peroxide vulcanizing agent; and / or the antioxidant is antioxidant RD; And / or the accelerator is accelerator M or accelerator DM.
5. The modified EPDM rubber according to claim 4, characterized in that: The peroxide vulcanizing agent is DCP or BIBP.
6. The method for preparing a modified EPDM rubber according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing EPDM rubber, plasticizer, vulcanizer, antioxidant, accelerator, co-crosslinking agent and reinforcing agent and kneading; (2) refining the rubber compound after internal mixing; (3) hot pressing and cold pressing the rubber material after kneading in sequence; (4) The molded rubber is mixed with α-olefin and irradiated with γ-rays to obtain α-olefin modified EPDM rubber.
7. The method for preparing a modified EPDM rubber according to claim 6, characterized in that: The refining temperature in step (1) is 100-120° C., the refining time is 10-30 min, and the refining speed is 10-50 rpm; And / or during the banburying in step (1), the EPDM rubber is first heated to the banburying temperature, and then a plasticizer, a vulcanizing agent, an antioxidant, an accelerator, a co-crosslinking agent and a reinforcing agent are added and mixed; And / or place at 20-35℃ for 24-48h after honey refining.
8. The method for preparing a modified EPDM rubber according to claim 6, characterized in that: In step (2), the rotation speed ratio of the front and rear rollers during the training is 1 to 2:1; And / or in step (2), the temperature of the opening refining is 90-100°C; And / or in step (2), the mill is thinned at least 5 times during the refining.
9. The method for preparing a modified EPDM rubber according to claim 6, characterized in that: In step (3), the temperature of the hot pressing molding is 100-120° C., the time of the hot pressing molding is 1-5 min, and the pressure of the hot pressing molding is 10-50 MPa; And / or in step (3), the temperature of the cold press molding is 20-30° C., the time of the cold press molding is 1-5 min, and the pressure of the cold press molding is 10-50 MPa.
10. The method for preparing a modified EPDM rubber according to claim 6, characterized in that: In step (4), before irradiating with gamma rays, the formed rubber material is mixed with the α-olefin and allowed to stand for 48 to 72 hours; And / or in step (4), the irradiation dose of gamma rays is 10 to 300 kGy; and / or in step (4), the gamma ray has an activity of 2.59×10 15 Bq 60 Co γ-rays; And / or in step (4), the irradiation dose rate of gamma rays is 100 Gy / min.
11. Use of a modified EPDM rubber obtained according to any one of claims 1 to 5 or any one of claims 6 to 10 for preparing low temperature resistant and / or high temperature resistant materials, wherein the low temperature is -48.1°C to -40°C and the high temperature is 89°C to 158°C.
12. A material, characterized in that The raw material comprises modified ethylene propylene diene monomer rubber obtained by the method according to any one of claims 1 to 5 or any one of claims 6 to 10.
Citation Information
Patent Citations
Preparation process of ethylene propylene diene rubber foaming materials
CN101824189A
Irradiation-resistant, low-smoke, halogen-free and flame-retardant sheath material for nuclear-grade cables
CN106566089A
High and low temperature compression deformation resistant EPDM rubber and preparation method thereof
CN117004142A
EPDM for Nuclear Power Plant with Hard Clay for Improvement of Resistant Radiation, and Mixing Method thereof
KR1020120047063A